Potential use of safer injecting facilities among injection drug users in Vancouver's Downtown Eastside - Kerr, Thomas (2003)
BACKGROUND: The Vancouver Coastal Health Authority will initiate North America's first sanctioned safer injecting facility, as a pilot project, on Sept. 15, 2003. The analyses presented here were conducted to estimate the potential use of safer injecting facilities by local illicit injection drug users (IDUs) and to evaluate the potential impact of newly established Health Canada restrictions and current police activities on the use of the proposed facility. METHODS: During April and May 2003, we recruited active IDUs in Vancouver's Downtown Eastside to participate in a feasibility study. We used descriptive and univariate statistics to determine potential use of a safer injecting facility and to explore factors associated with willingness to use such a facility with and without federal restrictions and police presence. RESULTS: Overall, 458 street-recruited IDUs completed an interviewer-administered survey, of whom 422 (92%) reported a willingness to use a safer injecting facility. Those expressing willingness were more likely to inject in public (odds ratio [OR] 3.9, 95% confidence interval [CI] 1.9–8.0). When the restrictions in the Health Canada guidelines were considered, only 144 (31%) participants were willing to use a safer injecting facility. IDUs who inject alone were more likely (OR 1.8, 95% CI 1.0–3.1) and women were less likely (OR 0.6, 95% CI 0.4–0.9) to be willing to use a safer injecting facility operating under these restrictions. Only 103 (22%) of the participants said they would be willing to use a safer injecting facility if police were stationed near the entrance. INTERPRETATION: Most IDUs participating in this study expressed a willingness to use a safer injecting facility. However, willingness declined substantially when the IDUs were asked about using a facility operating under selected Health Canada restrictions and in the event that police were stationed near the entrance.